DINAMIKA SPASIAL PEMANFAATAN LAHAN OLEH MASYARAKAT DAERAH ALIRAN SUNGAI (DAS) KREO (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Landuse dynamics of Kreo watershed from the result of interpretation of satellite image landsat (the year 1994) and image SPOT-5 (the year 2006) in the form of degradation of open farm wide of 67,07%, coppice 9,61%, forest 6,69%, and rice feld 4,64%; improvement of plantation wide 24,42%, setlement 21,68%, and mixture garden with a width of 1,05%. Forest wide and plantation of DAS Kreo only with a width of 17,19% had not pursuant to ideal wide of minimum forest of 30% at one particular in watershed (PP number 33 the year 1970). Wide area of setlement in Kreo watershed with a width of 12,21% is including category has exceeded ideal boundary of setlement area at one particular in watershed, maximum boundary (threshold) in the form of area of waterproof equal to 6%-10% in watershed.Keywords: Landuse spatial dynamic, landuse trend.